Proposal of Metrics for Business Networks Competitiveness Evaluation: a case in the Brazilian Steel Industry - Rodrigues, Felipe Augusto Messias; Boaventura, João Maurício Gama; Pereira, Cristina Espineira Costa; Cassanego Júnior, Paulo (Revista de Administração da UFSM, 2014)
Business Networks (BN) are systems formed by companies that interact in specific way, and the result of these interactions is a remarkable ability to compete. The object of this research is the analysis of the competitiveness in BN, and the objective is to develop metrics for analysis of the competitiveness in BN. This is a qualitative descriptive research, and uses primary sources (questionnaires and semi-structured interviews) and secondary sources of information (articles and other publications in the area). From the model of analysis of competitiveness proposed by Zaccarelli et al. (2008), procedures were performed to analyze the feasibility of applying the original metric of the model and new metrics were developed when necessary. The evaluation of metrics was possible after the empirical analysis, which consisted of the application of the model in two steel makings BN, the ArcelorMittal BN and Votorantim Steel BN. It was found that the metrics of six of ten fundamentals of the model of Zaccarelli et al. (2008) had impracticable metrics, subsequently, new metrics were developed and tested. The main contribution of this study was the improvement of the model, which will enable advances in the analysis of competitiveness business network.